1906 Miss. Laws 367, ch. 114, § 3887. - (:unkn) unknown (General Publisher, 1906)
On each person or firm dealing in pistols, dirk knives, sword canes, brass or metallic knuckles, or other deadly weapons (shotguns and rifles excepted) - 100.00. And which shall be in addition to all and any other taxes or privileges paid. On each firm or dealer selling air guns, target or flobert rifles (and this shall apply even if the same has a license to sell merchandise, pistols or cartridges) - $25.00.
--
Keywords: TAX - DEALERS